Expression, purification, and oligomerization of phosphoprotein of nipah virus - Salvamani, Shamala (2013)
Nipah virus (NiV) is a single-stranded, non-segmented negative-sense RNA virus belonging to genus Henipavirus. NiV causes fatality to humans and various types of animals. Its genome encodes six major structural proteins: nucleocapsid (N), phospho (P), matrix (M), fusion (F), glyco (G) and large (L) proteins. The P protein is vital for the genome replication and transcription. The potential diagnostic utility of the purified recombinant NiV P protein was determined in this study. In addition, the oligomeric nature of the P protein was also explored through its multimerization domain. Previously, the NiV P gene (2124 bp) was cloned into pTrcHis2-TOPO vector. In the present study, the P protein (120 kDa) was expressed in Escherichia coli and the optimal expression conditions such as the cultivation temperature, concentration of IPTG and the time of post-induction were determined in order to express the P protein in soluble form. SDS-PAGE and Western blot analysis using the anti-His antibody confirmed the protein expression. The optimum cultivation temperature for the recombinant protein expression was at 37 ºC while the optimum induction time was at 9 h with 1 mM IPTG. Solubility analysis showed that about 70% of the P protein was in soluble form at 37 ºC. An immobilized metal affinity chromatography (IMAC) was used to purify the recombinant P protein from the clarified E. coli homogenate. The purity of elution after HisTrap purification was 92.67% with a purification factor of 11.58. ELISA and Western blot analysis confirmed that the P protein was antigenic and could be used in serodiagnosis for detecting anti-P antibody of NiV infections. The oligomerization of P protein plays essential roles in the transcription and replication cycle of NiV. The full length P protein has different phosphorylation status which leads to the existence of more than one protein band in SDS-PAGE and Western blot, it is very difficult to determine the oligomeric nature of the P protein. Thus, the phosphoprotein multimerization domain (PMD) of NiV, which is responsible for the formation of oligomers, was cloned into pTrcHis2-TOPO vector, expressed in E. coli and purified with His-Trap column. A stepwise elution protocol was used in order to obtain purer recombinant PMD protein which yielded about 96.73% purity. The purified PMD protein was subjected to chemical cross-linking and dynamic light scattering analyses. The result confirmed that the PMD protein of NiV form tetramers. Circular dichroism analysis revealed that the PMD domain has a high α-helical content, about 55%. This study demonstrated the potential of NiV P protein as a diagnostic reagent for the detection of NiV infections and the oligomeric state of its multimerization domain.